ChemInform Abstract: A New Flavonoid Glycoside and Four Other Chemical Constituents from Viscum coloratum and Their Antioxidant Activity. Issue 44 (4th November 2014) - Yu, Zhiguo; Zhao, Yunli; Fan, Ronghua; Ma, Yuying; Yuan, Hongxia; Zhang, Yongzhi; Wei, Binbin
Abstract isolation, structure elucidation and in vitro antioxidant activity of the new flavonoid glycoside (I) and four known compounds